Swallowing rehabilitation following spinal injury: A case series. (2nd January 2022) - Dick, Shaolyn; Thomas, Jess; McMillan, Jessica; Davis, Kelly; Miles, Anna
Abstract : Context/objective: Swallowing difficulties (dysphagia) are well recognized after spinal injury. There are no published rehabilitation efficacy studies to date. This study explored viability and outcomes of swallowing rehabilitation programs for four patients with persisting dysphagia. Design: Prospective, quantitative experimental longitudinal case series. Setting: Spinal rehabilitation unit or patients' homes. Interventions: Four patients engaged in a 6-week (3×weekly) individualized progressive rehabilitation program. Outcome measures: Objective videofluoroscopic measures of timing and displacement and a validated self-reported questionnaire – the Eating Assessment Tool (EAT-10) were taken pre-therapy, immediately post-therapy and EAT-10 was repeated at 3 months. Feeling and fatigue scale scores were taken before and after each therapy session. Results: Patients (63, 67 yr, 67 yr, 76 yr; 3 male) had varying spinal diagnoses (2 traumatic, all involving the C-spine) and length of dysphagia (6 weeks, 6 weeks, 12 weeks, 10 yr). Common physiological impairments across all patients were: reduced maximum hyoid displacement, reduced pharyngeal constriction and reduced pharyngoesophageal segment maximum opening. Therapy programs were well received with 100% compliance. Participants made quantitative improvements in their videofluoroscopic measures of timing and displacement. Three out of four participants were able to have their percutaneous endoscopic gastrostomies (PEG) removed. EAT-10 scores significantly improved for all patients ( P  < .001). Poor upper limb function and restricted neck flexion prohibited some exercises. Conclusions: For many patients following spinal injury, dysphagia resolves during the acute phase of post-surgery recovery. For some, significant pharyngeal impairments persist. This case series demonstrates potential to regain functional swallowing following a 6-week tailored rehabilitation program. High-quality research exploring efficacy of rehabilitation programs are warranted.